EVALUATION OF ANALGESIC AND ANTI-INFLAMMATORY ACTIVITY OF DIOSPYROS CORDIFOLIA EXTRACT - Das, S.; Haldar, P. K.; Pramanik, G.; Panda, S. P.; Bera, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
In this study we evaluated the analgesic and anti- inflammatory activities of the methanol extract of stem bark of Diospyros cordifolia (MEDC) Roxb. The analgesic effects of the stem bark of the plant was assessed in mice using the tail-flick method while carrageenan, histamine and dextran induced paw oedema was used to study the antiinflammatory effects in rats. The MEDC exhibited significant (p<0.01) analgesic effects comparable to the reference drug diclofenac sodium. MEDC also was evaluated for its anti-inflammatory potential against carrageenan, histamine and dextran induced rat paw edema. The methanol extract (25 and 50 mg / kg body weight) exhibited significant (p<0.01) activity against all phlogistic agents used in a dose dependent manner. All these effects were compared with reference drug phenylbutazone (100 mg/kg body weight).